Exploring The Impact of Capecitabine Treatment on Hormonal and Biochemical Markers in Women with Breast Cancer - Masoudi, Raaid Fadhl Abbas; Ahmed Salih Sahib; Hasanain Shakir Mahmood; Karar Kadhim Mohsin; sultan, Ali Amal Aldeen Majeed (Iraqi Journal of Pharmaceutical Sciences, 2023)
Cancer antigen 15-3 (CA15-3) is a widely used tumor marker, and the serum level of this tumor marker is measured periodically in breast cancer patients during the chemotherapy period by capecitabine , Assuming that the higher serum levels of this tumor marker can be a potential risk in breast cancer patients, the study aimed to examine the effect on capecitabine with Ca15.3, serum estradiol, and calcium levels in postmenopausal women with breast cancer. The study was conducted on a total of 200 women, including 100 women without breast cancer who served as a control group aged range from (45-75years) and 100 women with breast cancer whose ages ranged from (40-70years). Patients at the oncology center at Imam al-Hussain medical city in Kerbala, Iraq, were sorted into groups based on their age, body mass index, disease duration, and treatment length for this study, which was done between July 2022 and October 2022, the efficacy of capecitabine, the plasma levels of (estradiol, Ca 15.3, and calcium) were measured in 100 breast cancer patients who had been taking the drug for at least 3 months. The findings revealed a statistically significant increase (p 0.05) in the concentration of Ca15.3 levels in women with breast cancer compared with control group, breast cancer (BC) is the most common form of cancer that results, and the average levels of serum calcium and estradiol were increased in patient had breast cancer chemotherapy and different with normal range, otherwise, the average level of serum calcium and estradiol in control groups within the normal range.in conclusion According to the ca15.3,serum calcium and estradiol levels, The high stability and existence of Ca15.3, serum calcium and estradiol in body serum make them a promising new diagnostic biomarker for breast cancer patients.